Odpowiedzi

2009-12-13T15:46:36+01:00
Z wzorów skróconego mnożenia:
(a+b)²= a²+2ab+b²
(a-b)²= a²-2ab+b²

a) (x-1)²-(x+4)²= -2x+1
x²-2x+1-(x²+8x+16)= -2x+1
x²-2x+1-x²-8x-16= -2x+1
-10x-15=-2x+1
-8x=16 /:(-8)
x=-2

b) (x+5)²-(x-3)²=x+1
x²+10x+25 -( x²-6x+9)=x+1
x²+10x+25 -x²+6x-9= x+1
16x+16=x+1
15x=-15 /:15
x= -1

c) (x -5)²-(x-3)²=4(x-2)
x²-10x+25 -( x²-6x+9)= 4x-8
x²-10x+25-x²+6x-9= 4x-8
-4x+16=4x-8
-8x= -24 /:(-8)
x=3
1 2 1
Najlepsza Odpowiedź!
2009-12-13T15:55:42+01:00
2 razy to samo zadanie? :))

a) (x-1)²-(x+4)²= -2x+1
x²-2x+1-x²-8x-16= -2x+1
-8x-15=1
-8x=16
x=-2

b) (x+5)²-(x-3)²=x+1
x²+10x+25-x²+6x-9=x+1
15x=1+9-25
15x=-15
x=-1

c) (x -5)²-(x-3)²=4(x-2)
x²-10x+25-x²+6x-9=4x-8
-8x=-24
x=3
1 5 1